Preoperative predictors for the presence of motile spermatozoa in the epididymis and patency of anastomosis during microsurgical vasoepididymal anastomosis in patients with obstructive azoospermia - Bhopesh Kadian; Aditya Prakash Sharma; Manish Rohilla; Ujjwal Gorsi; Japleen Kaur; Ravimohan S Mavuduru (Wolters Kluwer Medknow Publications, 2023)
Background: Following microsurgical vaso-epididymal anastomosis (VEA), anastomotic patency with sperm returning to the ejaculate is not always present and may even be delayed. The presence of motile spermatozoa is highly suggestive of future patency following surgery. Aims: We prospectively analyse the factors that could predict motile spermatozoa at the epididymis intraoperatively and predictors of patency in patients with obstructive azoospermia (OA) undergoing microsurgical VEA. Settings and Design: Department of Urology of a tertiary care centre in Northern India. It is a prospective observational study. Materials and Methods: Over a 2-year period (July 2019 to June 2021), 26 patients with idiopathic OA were enrolled in the study. Twenty patients underwent microsurgical VEA. Patients were divided into two groups based on the presence/absence of intraoperative motile spermatozoa. Statistical Analysis Used: Analysis of preoperative and intraoperative factors was done using the Mann-Whitney U-test, Chi-squared test and Fischer exact test. Results: Out of 20 patients, 5 (group 2) had intraoperative motile spermatozoa in the epididymal fluid and 15 (group 1) had nonmotile spermatozoa. Low luteinising hormone (LH) levels (P = 0.01) and high testosterone levels (P = 0.05) were the predictive of presence of motile spermatozoa in epididymal fluid. Mean follow-up was 9 months (6-18 months). Predictors of higher patency were grade 2 epididymis (firm, turgid and tense) (P = 0.003), low LH levels (P = 0.03), low sertoli cell index (P = 0.006), high sperm-Sertoli index (P = 0.002) and better surgeon satisfaction (P = 0.01). Conclusion: Low LH levels and high testosterone levels may be predictive of the presence of motile spermatozoa in epididymal fluid. Firm, turgid and tense epididymis, low Sertoli cell index, high sperm-Sertoli index and surgeon satisfaction suggest a greater chance of success after VEA for idiopathic azoospermia.